THE ROLE OF PHILOSOPHY IN NATIONAL-STATE CONSTRUCTION AND DEVELOPMENT OF THE REGION - Iskandarova D.M (Galaxy International Interdisciplinary Research Journal, 2022)
The real history of philosophy shows that the ancient traditions of practical, in particular, political philosophy are continued to receive additional material in favor of its effectiveness in modern scientific literature. Living proof of the prospects of practical philosophy appears as the postmodern phase of the development of philosophy. The article deals with the role of philosophy in the national-state construction and development of Dagestan in the era of globalization. The purpose of the regional practical philosophy is the formation of the methodology of socio-cultural and national strategy in the main directions, means, and terms of implementation of management decisions by the leadership of Dagestan. Their practical result is sustainable development, determination of economic and ecological ways and mechanisms of development in the epoch of globalization, and specification of ways of exit from the socio-cultural crisis of Daghestan, his spiritual revival.